Avaliação da intensidade luminosa na germinação e no desenvolvimento iniciaç de leucena (Leucaena leucocephala (Lam) de Wit.) - Decker, Vanessa (2008)
The study objective was to evaluate the effects of light intensities upon the initial development of Leucaena leucocephala seedlings. The study was conducted inside a preservation area around a drinking water well used to supply Marechal Cândido Rondon residents from September, 11st to November, 20st . Seeds collected from mature leucaena trees located on adjacent county (Toledo) were scarifyed and sown in vases. The vases were distributed in the area obeying a entirely randomized design with 13 light intensities (treatments) and 10 replications (vases) totalizing 130 vases. Five and two seedlings per vase were left after thinning executed 10 and 20 daysafter sowing, respectively. Sixty days after the sowing, seedlings were collected for measurements of stem diameter, plant height, number and area of leaves, as well as root, stem and leaves biomasses. Results indicated to exist a polynomial relationship of fourth order between biometric parametersand light intensity; highest significances were calculated for intensities of 643 and 2273 Lux indicating that leucaena can be considered pioneering and tolerant to direct sunlight